“I Have Been Reading Your Adventures for Years!”: Explicit and Implicit Metatextuality in Comic Books - Martin, Côme (Recherches sémiotiques / Semiotic Inquiry, 2017)
This article aims to analyze the ways comics can represent their own mode of discourse, through the use of implicit or explicit metatextual devices. I begin by examining the relation of comics with architecture. Through a few selected examples, I show how a door, a window, or the façade of a building can serve as discreet metonymies for the layout of a comic book’s pages and panels. I follow up by considering instances where a comic book is represented within the fictional world of the narrative, usually through a character who serves as surrogate reader whithin the diegesis.In both cases, the use of metatextuality foregrounds how comics work and what their specificities are, starting with their ergodic and fragmentary character.